2021
DOI: 10.1021/acsfoodscitech.0c00075
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Influence on the Dynamics of the Human Gut Microbiome: Prospective Implications in Interventional Therapies

Abstract: Dietary factors have a significantly influential role in regulating body homeostasis by modulating gut microbial composition, supplying different sources of nutrients, and inducing changes in the body. Unhealthy short- or long-term modifications in the dietary pattern can alter the intestinal microbiota, leading to a loss of metabolic control and physiological activities, which is a growing concern as per recent studies. Diets, mainly containing high-fat, high-carbohydrate, and low-fiber content, are predispos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 272 publications
(544 reference statements)
0
7
0
Order By: Relevance
“…Not surprisingly, this was closely related to the altered host microbiome in PIBD patients, featuring changes in Escherichia-Shigella, Enterococcus , and SCFA-producing microbiota ( Solis et al, 2020 ). Another potential contributing factor is the host diet, as diet was recently found able to influence the human gut microbiome and the pathogenesis of IBD ( Adithya et al, 2021 ). A deeper investigation of the key species by metagenomic and metabolic sequencing may further improve our understanding of the early triggers in PIBD, enhance the performance of the diagnosis model, and provide new routes for the treatment of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, this was closely related to the altered host microbiome in PIBD patients, featuring changes in Escherichia-Shigella, Enterococcus , and SCFA-producing microbiota ( Solis et al, 2020 ). Another potential contributing factor is the host diet, as diet was recently found able to influence the human gut microbiome and the pathogenesis of IBD ( Adithya et al, 2021 ). A deeper investigation of the key species by metagenomic and metabolic sequencing may further improve our understanding of the early triggers in PIBD, enhance the performance of the diagnosis model, and provide new routes for the treatment of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic products of the abundant microbiota mostly affects the establishment of probiotic bacteria, can be supported with the use of prebiotics. Gut microbiota can be altered/modified using probiotics, prebiotics, synbiotics, and postbiotics such as (SCFAs), and all of these can contribute positively to host health (Adithya et al, 2021). Some prebiotics such as dietary polyphenols exert antimicrobial activities against pathogenic gut microbiota, improve gut metabolism and immunity, impart antiinflammatory properties, and also provide benefits in various gastrointestinal, metabolic, and neuropsychological disorders (Adithya et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota can be altered/modified using probiotics, prebiotics, synbiotics, and postbiotics such as (SCFAs), and all of these can contribute positively to host health (Adithya et al, 2021). Some prebiotics such as dietary polyphenols exert antimicrobial activities against pathogenic gut microbiota, improve gut metabolism and immunity, impart antiinflammatory properties, and also provide benefits in various gastrointestinal, metabolic, and neuropsychological disorders (Adithya et al, 2021). Interestingly, a recent study indicated that arabinoxylan can increase the relative abundance of Clostridium, while decrease the relative abundance of Desulfovibrio and Bilophila (Li et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…life style, gender, environmental changes) ( Conlon and Bird, 2015 ). Furthermore, the dietary type has been shown to be highly implicated in the microbiome structural composition ( Adithya et al., 2021 ). The type of diet modulates the abundance of altered bacteria in the gut microbiota at various stage of life.…”
Section: Human Microbiome and Healthy Statusmentioning
confidence: 99%
“…The type of diet modulates the abundance of altered bacteria in the gut microbiota at various stage of life. Individuals with high-fiber diets have their gut populated with beneficial microbes, which could exert health benefits, while the gut microbiome composition of those with high-fat and high-sugar diets are negatively altered ( Adithya et al., 2021 ). The diet patterns have been correlated to the host intestinal microbiota interaction with many metabolic processes, and is responsible in part in protecting or predisposing multiple metabolic, immunological, neoplastic, and functional diseases ( Schiumerini et al., 2018 ; Adithya et al., 2021 ).…”
Section: Human Microbiome and Healthy Statusmentioning
confidence: 99%